1993
DOI: 10.1152/ajpgi.1993.265.3.g482
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of the neurotensin gene in the developing rat and human gastrointestinal tract

Abstract: Neurotensin (NT) is an important hormone regulating gut motility, secretion, and growth. The purpose of this study was to determine the developmental expression of the NT/neuromedin N gene (NT/N) in the gut and pancreas of rats and humans. We found that NT/N expression, initially low in the fetal rat jejunum and ileum, is increased by postnatal day 3. This increase is independent of contact with luminal nutrients as demonstrated by elevated NT/N expression in rat jejunoileal grafts implanted in nude mice. NT/N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
16
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…The primary sequences of both the rat and human genes encoding NT and the structurally related hexapeptide, neuromedin N, have been elucidated (19,20). In the GI tract, the NT/neuromedin N (NT/N) gene is developmentally regulated in the human and rat intestines in a temporospatial manner (21)(22)(23). The promoter proximal 5Ј-flanking region of the rat NT/N gene has previously been shown to integrate multiple environmental stimuli in neuroendocrine PC12 cells and to be sufficient for cell-specific expression in enteroendocrine BON cells (24,25).…”
mentioning
confidence: 99%
“…The primary sequences of both the rat and human genes encoding NT and the structurally related hexapeptide, neuromedin N, have been elucidated (19,20). In the GI tract, the NT/neuromedin N (NT/N) gene is developmentally regulated in the human and rat intestines in a temporospatial manner (21)(22)(23). The promoter proximal 5Ј-flanking region of the rat NT/N gene has previously been shown to integrate multiple environmental stimuli in neuroendocrine PC12 cells and to be sufficient for cell-specific expression in enteroendocrine BON cells (24,25).…”
mentioning
confidence: 99%
“…NT facilitates translocation of fatty acids in the proximal including secretion, motility, and gut mucosal growth (28)(29)(30)(31)(32)(33)(34)(35)(36). Expression of the gene encoding NT and the structurally related hexapeptide neuromedin N (designated NT/N) is developmentally regulated in the gut of both rat and human in a distinctive temporal-and spatial-specific distribution (37,38). NT/N expression is initially low in the fetus but rapidly increases after birth to assume the distinctive adult topographical distribution of increasing NT/N expression along the longitudinal axis of the small bowel.…”
mentioning
confidence: 99%
“…Using isolated gut segments from the rat implanted as xenografts in athymic nude mice, we recently demonstrated that the strict temporal-and spatial-specific pattern of NT/N expression is not affected by either location or luminal contents, thus suggesting an intrinsic program of NT/N gene expression (39). In the human colon, NT/N is transiently expressed during a developmental stage (midgestation) that is characterized by morphologic and functional similarity to the small bowel (40,41); however, expression of NT/N is not apparent in the colon of the newborn or the adult (37). Taken together, these studies identify the NT/N gene as an important endocrine model to better delineate the complex mechanisms leading to differentiation of the gut to either a small bowel or colonic phenotype.…”
mentioning
confidence: 99%
See 2 more Smart Citations